Methylation quantitative trait loci within the TOMM20 gene are associated with metabolic syndrome-related lipid alterations in severely obese subjects. Issue 1 (December 2016) - Toro-Martín, Juan; Guénard, Frédéric; Tchernof, André; Deshaies, Yves; Pérusse, Louis; Hould, Frédéric-Simon; Lebel, Stéfane; Marceau, Picard; Vohl, Marie-Claude
Abstract Background TheTOMM20 gene was previously identified as differentially expressed and methylated between severely obese subjects with and without metabolic syndrome (MS). Since metabolic complications do not affect all obese patients to the same extent, the aim of this study was to identify methylation quantitative trait loci (meQTL) potentially associated with MS-related complications within theTOMM20 locus. Methods Methylation profiling, SNP genotyping and meQTL association tests (general linear models) were performed in a population of 48 severely obese subjects. Genotyping was extended to a larger population of 1720 severely obese subjects with or without MS, where genotype- and diplotype-based association tests were assessed by logistic regression. In silico analyses were performed using TRAP. Results Four SNPs were identified as significant meQTLs for the differentially methylated site cg16490124. Individuals carrying rare alleles of rs4567344 (A > G) (P  = 4.9 × 10−2 ) and rs11301 (T > C) (P  = 5.9 × 10−3 ) showed decreased methylation levels at this site, whereas those carrying rare alleles of rs4551650 (T > C) (P  = 3.5 × 10−15 ) and rs17523127 (C > G) (P  = 3.5 × 10−15 ) exhibited a significant increase in methylation. rs4567344 and rs11301 were associated with increased susceptibility to exhibit high plasma triglycerides (TG ≥ 1.69 mmol/L), while rare alleles of rs4551650 and rs17523127 were significantly more represented in the low plasma total-C group (total-C ≤ 6.2 mmol/L). Haplotype reconstruction with the four meQTLs (rs4567344, rs11301, rs4551650, rs17523127) led to the identification of ten different diplotypes, with H1/H2 (GCGG/ACGG) exhibiting a nearly absence of methylation at cg16490124, and showing the highest risk of elevated plasma TG levels [OR = 2.03 (1.59–3.59)], a novel association with elevated LDL-cholesterol [OR = 1.86 (1.06–3.27)] and the complete inversion of the protective effect on total-C levels [OR = 2.03 (1.59–3.59)], especially in men. In silico analyses revealed that rs17523127 overlapped the CpG site cg16490124 and encompassed the core binding sites of the transcription factors Egr 1, 2 and 3, located within theTOMM20 promoter region. Conclusion This study demonstrates thatTOMM20 SNPs associated with MS-related lipid alterations are meQTLs potentially exerting their action through a CpG methylation-dependent effect. The strength of the diplotype-based associations may denote a novel meQTL additive action and point to this locus as particularly relevant in the inter-individual variability observed in the metabolic profiles of obese subjects.